2020
DOI: 10.1186/s40463-020-00477-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of fourth branchial apparatus anomalies: A case series study

Abstract: Background Fourth branchial apparatus anomalies, are rare clinical entities, and present as complex cysts, sinuses and fistulae in the neck that can be difficult to manage. Methods This is a retrospective review of a series of consecutive patients with fourth branchial apparatus anomalies treated at Department of Otolaryngology Head and Neck Surgery, Beijing Friendship Hospital, Capital Medical University, from Apr 2014 to Nov 2019. Results Ten patients with fourth branchial apparatus anomalies were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“… 1 PSC is commonly identified during the newborn period and causes respiratory failure, neck abscess, or thyroiditis. 1 , 2 , 10 It originates from the failure obliteration of the third or fourth pharyngeal pouches, which are connected to the pharynx by the pharyngobranchial duct. 1 , 2 Owing to its rarity in neonates, the diagnosis and treatment of PSC remains complicated and not clearly described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 PSC is commonly identified during the newborn period and causes respiratory failure, neck abscess, or thyroiditis. 1 , 2 , 10 It originates from the failure obliteration of the third or fourth pharyngeal pouches, which are connected to the pharynx by the pharyngobranchial duct. 1 , 2 Owing to its rarity in neonates, the diagnosis and treatment of PSC remains complicated and not clearly described.…”
Section: Discussionmentioning
confidence: 99%
“…Complete removal of the fistula and cyst with or without affected thyroid tissue was previously the most commonly used and most thorough treatment. 1 , 2 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Third and fourth branchial anomalies are extremely rare entities and account for less than 1% of branchial malformations. 63 These lesions typically present as cystic structures at the lower, anterior border of the SCM at the level of the superior pole of the thyroid and manifest clinically as repeated episodes of neck swelling, abscess formation, and suppurative thyroiditis. 47,64 They are often diagnosed in childhood and occur predominantly on the left side with slight female predominance.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high recurrence rate, the general consensus remains that complete surgical resection via open or endoscopic techniques in a quiescent state is the definitive treatment for these lesions. 63,75,76 Studies have shown that partial thyroidectomy can further reduce recurrence rates as branchial remnants and cysts may be found partly or completely enveloped in thyroid tissue. 67 Meticulous dissection is necessary to visualize and avoid injury to the superior and recurrent laryngeal nerves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation